Non-drinking and social life in adolescence: a qualitative study in Switzerland - Lorraine Chok; Joan-Carles Suris; Lucie Vittoz; Diana Fernandes Palhares; Yara Barrense-Dias (Discover Social Science and Health)
Abstract Background Alcohol consumption is popular among adolescents and young people and adolescent non-drinkers may be socially excluded and/or stigmatized. The aim of this qualitative study was to explore the social life of young non-drinkers (14–20 years old), to understand how they live their non-drinking and how they are perceived by their drinking peers. Methods We conducted a qualitative research on non-consumption of alcohol in the French-speaking region of Switzerland. Our study included 63 young people divided into 12 focus groups aged 14 to 20 years. Results Overall, young non-drinkers would be a minority in their peer groups, leading some of them to feel out of the norm. Participants reported that not drinking alcohol is generally questioned and non-drinkers are almost always asked to justify their non-consumption. Finally, non-drinkers are sometimes automatically designated as resources who have to control the drinking of others and/or are the ones who help their drinking-peers if they are drunk and need help, a status that can put them under pressure. Conclusions It is important to normalize the non-consumption of alcohol and make non-drinkers visible by including them in school-based prevention interventions.